Structural basis for recruitment of the ATPase activator Aha1 to the Hsp90 chaperone machinery - Meyer, Philippe (2004)
Hsp90 is a molecular chaperone essential for the activation and assembly of many key eukaryotic signalling and regulatory proteins. Hsp90 is assisted and regulated by co-chaperones that participate in an ordered series of dynamic multiprotein complexes, linked to Hsp90s conformationally coupled ATPase cycle. The co-chaperones Aha1 and Hch1 bind to Hsp90 and stimulate its ATPase activity. Biochemical analysis shows that this activity is dependent on the N-terminal domain of Aha1, which interacts with the central segment of Hsp90. The structural basis for this interaction is revealed by the crystal structure of the N-terminal domain (1–153) of Aha1 (equivalent to the whole of Hch1) in complex with the middle segment of Hsp90 (273–530). Structural analysis and mutagenesis show that binding of N-Aha1 promotes a conformational switch in the middle-segment catalytic loop (370–390) of Hsp90 that releases the catalytic Arg 380 and enables its interaction with ATP in the N-terminal nucleotide-binding domain of the chaperone.